2007
DOI: 10.1021/ol701730r
|View full text |Cite
|
Sign up to set email alerts
|

Amination of Heterocyclic Compounds with O-Benzoylhydroxylamine Derivatives

Abstract: The N-amination of heterocyclic compounds 1a-k with O-benzoylhydroxylamine derivatives 5 was developed and demonstrated to be a superior alternative to existing N-amination methods. A structure-reactivity relationship study was performed on variously substituted O-benzoylhydroxylamine derivatives, leading to the discovery of the novel and more efficient aminating reagents 5h and 5i.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…18 Deprotonation of 14 with NaH (DMF) followed by addition of monochloroamine (ClNH 2 in ether, 30 min, 23 °C) provided the N-aminopyrazole 15 in superb conversions (88–93%) that was oxidized with NaIO 4 (2 equiv, CH 2 Cl 2 –H 2 O, 2 h) at room temperature to provide 3 (81%). Although this synthesis was used to prepare most of 3 employed in our studies, we have more recently found that the N-amination of 14 to provide 15 may be accomplished even more conveniently with O -(4-nitrobenzoyl)hydroxylamine 19 (1.1 equiv of KOBu t , NMP, 20 min, 22 °C; 1.15 equiv of O -(4-nitrobenzoyl)hydroxylamine, NMP, 22 °C, 2 h, 75%). 5-Carbomethoxy-1,2,3-triazine proved to be especially reactive and was found to be sensitive to water.…”
Section: Resultsmentioning
confidence: 99%
“…18 Deprotonation of 14 with NaH (DMF) followed by addition of monochloroamine (ClNH 2 in ether, 30 min, 23 °C) provided the N-aminopyrazole 15 in superb conversions (88–93%) that was oxidized with NaIO 4 (2 equiv, CH 2 Cl 2 –H 2 O, 2 h) at room temperature to provide 3 (81%). Although this synthesis was used to prepare most of 3 employed in our studies, we have more recently found that the N-amination of 14 to provide 15 may be accomplished even more conveniently with O -(4-nitrobenzoyl)hydroxylamine 19 (1.1 equiv of KOBu t , NMP, 20 min, 22 °C; 1.15 equiv of O -(4-nitrobenzoyl)hydroxylamine, NMP, 22 °C, 2 h, 75%). 5-Carbomethoxy-1,2,3-triazine proved to be especially reactive and was found to be sensitive to water.…”
Section: Resultsmentioning
confidence: 99%
“…6 The tedious workup procedure and isolation of highly polar, water-soluble hydrazines is the major disadvantage of this method. However, N-amination of heterocycles can be achieved by O-(diphenylphosphinyl)hydroxylamine, 7 chloramine, 8 or by Oarylhydrroxylamines 9 with isolated yields ranging from 45-97%. Oxaziridine derivatives 1, 10 2, 11 and 3 4 were used as very good reagents for electrophilic amination of alkyl amines and amino acid derivatives.…”
Section: Scheme 1 Synthetic Applications Of B-boc-hydrazinesmentioning
confidence: 99%
“…[16][17][18][19] Synthesis of 9-(6-Bromohexyl)-9H-carbazole (1) 1,6-Dibromohexane (29.2 mL, 180 Â 10 À3 mol) was added to a mixture of carbazole (10 g, 60 Â 10 À3 mol) with N,N-dimethylformamide (DMF) (200 mL) and KOH at 0 8C. The reaction mixture was stirred at room temperature for 48 h. The organic layer was poured into water and extracted with diethyl ether.…”
Section: Procedures For the Synthesis Of Polymersmentioning
confidence: 99%
“…Procedures for the Synthesis of Polymers 3,6-Dibromo-9H-carbazole, 3,6-dibromo-9-hexyl-9H-carbazole, 9-hexyl-3,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-9H-carbazole, and 2,2 0 -(9,9-dioctyl-9H-fluorene-2,7 0 -diyl)bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane) were synthesized using a slight modification of the method reported in the literature. [16][17][18][19] Synthesis of 9-(6-Bromohexyl)-9H-carbazole (1) 1,6-Dibromohexane (29.2 mL, 180 Â 10 À3 mol) was added to a mixture of carbazole (10 g, 60 Â 10 À3 mol) with N,N-dimethylformamide (DMF) (200 mL) and KOH at 0 8C. The reaction mixture was stirred at room temperature for 48 h. The organic layer was poured into water and extracted with diethyl ether.…”
Section: Materials and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation